(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have studied the effects of the externally applied electric and magnetic fields on Bose-Einstein condensation of the charged Bose gas. We have used a model density of states which takes the finite sample size into account to calculate the thermodynamic quantities. We have obtained condensate fraction, chemical potential, total energy and specific heat of the system using the semi classical density of states. We have studied the possibility for achieving Bose-Einstein condensation in three dimensional non interacting charged Bose gas under the cross electric and magnetic fields. The external fields made the system inhomogeneous and altered the Bose-Einstein condensation characteristics compared to the homogeneous case. We have found that the non interacting system of charged boson undergo Bose- Einstein condensation when external electric and magnetic fields were applied. The discontinuity in the specific heat was found as a function of external potentials. The obtained results were found in good agreement with previously obtained results.